2010
DOI: 10.1002/ajpa.21290
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of native circumpolar populations based on autosomal, mitochondrial, and Y chromosome DNA markers

Abstract: This study investigates the genetic structure of the present-day inhabitants of Beringia in order to answer questions concerning their origins and evolution. According to recent studies, the ancestors of Native Americans paused for a time in Beringia, during which they differentiated genetically from other Asians before peopling the New World. Furthermore, the Koryaks of Kamchatka share a "ubiquitous" allele (D9S1120) with Native Americans, indicating they may have descended from the same ancestral Beringian p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…Generally, these results coincide with the results of many studies carried out at the regional rather than global level which have revealed low to medium and mostly non-significant correlations between genetic distances based on different systems (Jorde et al, 2000;Lum et al, 1998), while many other studies report discordance in results when different polymorphisms are used in population genetic studies of the same groups (Passarino et al, 1998;P erez-Lezaun et al, 1999;Jorde et al, 2000;Wilder, 2004;Rubicz et al, 2010;Aim e et al, 2015). But despite this there is a certain similarity between three sources of genetic data-mtDNA, autosomal SNP and cranial non-metrics-which is clearly visible when correlation structure of all the studied matrices is considered (Fig.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Generally, these results coincide with the results of many studies carried out at the regional rather than global level which have revealed low to medium and mostly non-significant correlations between genetic distances based on different systems (Jorde et al, 2000;Lum et al, 1998), while many other studies report discordance in results when different polymorphisms are used in population genetic studies of the same groups (Passarino et al, 1998;P erez-Lezaun et al, 1999;Jorde et al, 2000;Wilder, 2004;Rubicz et al, 2010;Aim e et al, 2015). But despite this there is a certain similarity between three sources of genetic data-mtDNA, autosomal SNP and cranial non-metrics-which is clearly visible when correlation structure of all the studied matrices is considered (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…1). In many previous studies of population genetics this marker system has also been shown to differ from other polymorphisms (Kittles et al, 1999;Wilder, 2004;Rubicz et al, 2010;Aim e et al, 2015). The Y-chromosome matrix is also peculiar in being significantly correlated with the climatic distance matrix and some morphological Bold values indicate "significant at P < 0.05".…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Several factors may have contributed to this discontinuity: The climatic changes that led to the deglaciation and the inundation of central Beringia between ;13 and 10 kya (Schurr et al 1999;Zlojutro et al 2006;Kitchen et al 2008;Volodko et al 2008) and continued through the present interstadial (Hu et al 2001) probably caused a great proportion of the only less than 2000 effective source population individuals to move from the harsh conditions once a viable alternative in the south was present (Kunz and Reanier 1994;Kitchen et al 2008;Mulligan et al 2008), likely giving rise to multiple further replacements, extinctions, and (re-)expansions that reshaped the genetic variation of the population groups in different refugia (Schurr et al 1999;Schurr 2004;Zlojutro et al 2006;Volodko et al 2008). Native tribes have been decimated on both rims of the former Beringia due to oppression, warfare, epidemics, forced relocations, and admixture since the 18th Century (Schurr et al 1999;Zlojutro et al 2006Zlojutro et al , 2009Rubicz et al 2010).…”
mentioning
confidence: 99%
“…Y-chromosome analysis was performed on 11 commonly used short tandem repeats (STRs): DYS19, DYS389I, DYS389II, DYS390, DYS391, DYS392, DYS393, DYS385A, DYS385B, DYS438, and DYS439, available in the Y-PLEX 12 Kit from ReliaGene Technologies Inc. (Rubicz et al 2010). The following single nucleotide polymorphisms (SNPs), defining Y-chromosome haplogroups, were characterized for the male samples: P39 (haplogroup C), P2 (haplogroup E), M170 (haplogroup I), 12f2 (haplogroup J), M231 (haplogroup N), P36 (haplogroup Q), and M269 and SRY 10381b (haplogroup R).…”
Section: Dna Analysismentioning
confidence: 99%